Matric suction of compacted soils - Ng, Teik Ting (2016)
This project covers the direct and indirect measurement of matric suction of compacted soil. The soil used in this project was Bukit Timah Granite residual soil. Residual soil was compacted with standard Proctor and modified Proctor effort. Matric suction measurements were conducted on the compacted soil specimens using the high capacity tensiometer (HCT), null-type axis-translation technique and chilled-mirror dew point device.